Klotho inversely relates with carotid intima- media thickness in atherosclerotic patients with normal renal function (eGFR ≥60 mL/min/1.73m2): a proof-of-concept study - Donate-Correa, Javier; Martín-Núñez, Ernesto; Martin-Olivera, Alberto; Mora-Fernández, Carmen; Tagua, Víctor G.; Ferri, Carla M.; López-Castillo, Ángel; Delgado-Molinos, Alejandro; López-Tarruella, Victoria Castro; Arévalo-Gómez, Miguel A.; Pérez-Delgado, Nayra; González-Luis, Ainhoa; et al. (Frontiers in Endocrinology, 2023)
Introduction Klotho protein is predominantly expressed in the kidneys and has also been detected in vascular tissue and peripheral blood circulating cells to a lesser extent. Carotid artery intima-media thickness (CIMT) burden, a marker of subclinical atherosclerosis, has been associated with reductions in circulating Klotho levels in chronic kidney disease patients, who show reduced levels of this protein at all stages of the disease. However, the contribution of serum Klotho and its expression levels in peripheral blood circulating cells and in the carotid artery wall on the CIMT in the absence of kidney impairment has not yet been evaluated. Methods We conducted a single-center study in 35 atherosclerotic patients with preserved kidney function (eGFR≥60 mL/min/1.73m2) subjected to elective carotid surgery. Serum levels of Klotho and cytokines TNFa, IL6 and IL10 were determined by ELISA and transcripts encoding for Klotho (KL), TNF, IL6 and IL10 from vascular segments were measured by qRT-PCR. Klotho protein expression in the intima-media and adventitia areas was analyzed using immunohistochemistry. Results APatients with higher values of CIMT showed reduced Klotho levels in serum (430.8 [357.7-592.9] vs. 667.8 [632.5-712.9] pg/mL; p<0.001), mRNA expression in blood circulating cells and carotid artery wall (2.92 [2.06-4.8] vs. 3.69 [2.42-7.13] log.a.u., p=0.015; 0.41 [0.16-0.59] vs. 0.79 [0.37-1.4] log.a.u., p=0.013, respectively) and immunoreactivity in the intimal-medial area of the carotids (4.23 [4.15-4.27] vs. 4.49 [4.28-4.63] log µm2 p=0.008). CIMT was inversely related with Klotho levels in serum (r= -0.717, p<0.001), blood mRNA expression (r=-0.426, p=0.011), and with carotid artery mRNA and immunoreactivity levels (r= -0.45, p=0.07; r= -0.455, p= 0.006, respectively). Multivariate analysis showed that serum Klotho, together with the gene expression levels of tumor necrosis factor TNFa in blood circulating cells, were independent determinants of CIMT values (adjusted R2 = 0.593, p<0.001). Discussion The results of this study in subjects with eGFR≥60mL/min/1.73m2 show that patients with carotid artery atherosclerosis and higher values of CIMT present reduced soluble Klotho levels, as well as decreased KL mRNA expression in peripheral blood circulating cells and Klotho protein levels in the intima-media of the carotid artery wall.